PENGARUH PENGGUNAAN LKPD DIGITAL BERBASIS HOTS TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI BANGUN DATAR KELAS V SEKOLAH DASAR - Jannah, Nurizzatul; Safiah, Intan; Vitoria, Linda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low level of students’ critical thinking skills in Mathematics, particularly on plane geometry material in Grade V at SD Negeri Lampeuneurut, is influenced by instructional materials that have not fully promoted higher-order thinking skills and the limited use of technology in learning. HOTS-based digital student worksheets (LKPD) are considered an alternative instructional material as they facilitate the development of students’ critical thinking skills. This study aims to determine the effect of using HOTS-based digital LKPD on students’ critical thinking skills. The study employed a quantitative approach with a quasi-experimental method using a Non-Equivalent Control Group design. The sample consisted of 44 students, with class VA as the experimental group and class VB as the control group. Data were collected through pretest and posttest assessments. Data analysis included N-Gain calculation, normality test, homogeneity test, and hypothesis testing using the Independent Samples t-Test. The results showed that the average N-Gain of the experimental class was higher than that of the control class, with a significance value of 0.001 < 0.05. Therefore, it can be concluded that the use of HOTS-based digital LKPD has a significant effect on students’ critical thinking skills.